Resistance and Rebellion on the Spanish Frontier: Native Responses to Colonization in the Colombian Chocó (2022)
eng: By the mid-sixteenth century, Spanish conquest of the major Indian societies in the Americas was more or less complete. There were, however, many indigenous societies that still remained outside the orbit of Spanish control, usually because they were in remote and inaccessible regions, had no obvious economic resources to exploit, or were able to mount effective resistance to Spanish incursions. Some of these societies continued to exist beyond the boundaries of the Iberian world throughout the colonial period; for others, those boundaries were broken down as Spanish colonial settlement expanded from its early bases and extended into regions that the Spaniards had initially found too difficult to colonize. Movements of this kind on the frontier of Spanish settlement occurred throughout Hispanic America, as missionaries and settlers carried Spanish influence and Spanish government into peripheral regions from northern Mexico to southern Chile.1 Frontier expansion of this kind also occurred in areas of New Granada (modern Colombia), where settlers pushed into previously uncolonized regions both to the east and to the west of the major settlements in the interior. One significant direction in which the frontier expanded was into the Choco, the large lowland region on New Granada's Pacific flank. Here, Spanish penetration was driven by both missionary zeal and, more powerfully, by the search for gold.